EUERGETISM, AGONISM, AND DEMOCRACY THE HORTATORY INTENTION IN LATE CLASSICAL AND EARLY HELLENISTIC ATHENIAN HONORIFIC DECREES. - Miller, Jacob (Hesperia)
From the late 4th century, the Athenians channeled the elite agonal spirit into euergetism by encouraging both the Athenian and the non-Athenian elite to compete in the provision of benefactions. The agonal spirit thus came to serve the polis, which received the benefactions it needed, as well as the elite, who received the honors and conspicuous self-distinction they wanted. An analysis of a dossier of some of the honorary decrees from 340-320 to 259/8 B.C. with hortatory elements reveals the strategy that lay behind these competitive exhortations, and emphasizes how the honors reflected contemporary needs and developments.